Chinese-English bilinguals prefer being truthful in the native language - Yang, Wenwen; Rauwolf, Paul; Frances, Candice; Molina-Nieto, Olivia; Duñabeitia, Jon Andoni; Thierry, Guillaume (Frontiers in Language Sciences, 2024)
Bilinguals make decisions differently across languages likely due to reduced affect in the foreign language, but very little is known about language use in relation to deception. Here, we tested whether late Chinese-English bilinguals prefer to lie in the foreign language when betting against a virtual opponent. In each trial, participants freely announced bets in Chinese or English depending on whether they had drawn a coin or not. Results showed that bilinguals preferred using their native language, Chinese, over their foreign language, English, when being truthful—namely, announcing a coin when they had one. Even though participants did not choose English more to lie than to tell the truth, our results can be interpreted as a tendency to lie more in English when their behaviour in the truth condition is considered the baseline. Participants also switched between languages more often after telling the truth than lying, and after telling the truth they switched more to Chinese. These results provide the first empirical evidence for strategic language use in bilinguals.